Pengaruh Pengetahuan Akuntansi, Tingkat Pendidikan, Motivasi Kerja dan Lama Usaha terhadap Informasi Akuntansi pada Pelaku UMKM (Studi pada Pelaku UMKM Mitra Mandiri) - Yuni Tri Rahayu; Roni Roni; Yenny Ernitawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to examine the effect of accounting knowledge, education level, work motivation, and length of business on accounting information in UMKM Mitra Mandiri actors. This research method is quantitative. The population is 120 businesses. The sample in this study is 55 respondents. The sampling technique uses the Slovin formula. Data analysis and hypothesis testing include validity testing, reliability testing and classical assumption testing. Data analysis uses multiple linear regression analysis. The results of this study indicate that accounting knowledge has an effect on accounting information in UMKM Mitra Mandiri actors. While the variables of education level, work motivation, and length of business do not affect accounting information in UMKM Mitra Mandiri actors.